The Orientalist poster : a century of advertising through the Slaoui Foundation collection / texts and coordination ; Abdelaziz Ghozzi. - Ghozzi, Abdelaziz ([I. B. Tauris], 1997)
19th-century Orientalist painting influenced other art forms, particularly poster art, which has since become highly collectable. One enthusiast's collection forms the basis of this book.